2020
DOI: 10.38212/2224-6614.1241
|View full text |Cite
|
Sign up to set email alerts
|

Acarbose attenuates migration/proliferation via targeting microRNA-143 in vascular smooth muscle cells under diabetic conditions

Abstract: Acarbose (an a-glucosidase inhibitor) has been demonstrated to reduce the progression of atherosclerosis without affecting serum levels of glucose in rabbits fed a high cholesterol diet. The main focus of recent atherosclerosis studies has been microRNA targets. However, the mechanism by which acarbose targets miRNA-mediated atherosclerosis remains unclear. This study aimed to evaluate the effect of acarbose on microRNA-related regulation of rat aortic vascular smooth cell line (A7r5 cell) migration and prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…In clinical trials lasting 12weeks or more, the HbA1c and glycemic responses typically demonstrated improvement over time while lipid profiles while improved, were less dramatic. [18][19][20][21][22][23][24][25][26][27][28][29] The results of this study are consistent with previous clinical findings, and confirm that the 8-week trial of feeding a highly palatable high carbohydrate sucroseladen diet to both lean and obese adult Wistar Fatty Rats with wellestablished NIDDM in the obese phenotype resulted in excess weight gain in both phenotypes, with the greatest gain by far among the obese+NIDDM phenotype. The SU diet also was associated with a predictable exaggeration of glycemic responses in the obese+NIDDM phenotype.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In clinical trials lasting 12weeks or more, the HbA1c and glycemic responses typically demonstrated improvement over time while lipid profiles while improved, were less dramatic. [18][19][20][21][22][23][24][25][26][27][28][29] The results of this study are consistent with previous clinical findings, and confirm that the 8-week trial of feeding a highly palatable high carbohydrate sucroseladen diet to both lean and obese adult Wistar Fatty Rats with wellestablished NIDDM in the obese phenotype resulted in excess weight gain in both phenotypes, with the greatest gain by far among the obese+NIDDM phenotype. The SU diet also was associated with a predictable exaggeration of glycemic responses in the obese+NIDDM phenotype.…”
Section: Discussionsupporting
confidence: 86%
“…13 The lipid profiles in the obese+NIDDM phenotype have been associated with increases in biochemical markers for free radical development and are clearly consistent with atherogenic lipid profiles, including elevations in both serum triglycerides and cholesterol, including the Low density (Alpha) lipoprotein fraction which have been associated with senescent alterations in the vascular intima. [29][30][31] Although the lipid parameters were not remarkably improved in the obese+NIDDM rats following the ACB treatment, the excess weight gain of obese+NIDDM rats consuming the high sucrose diet was improved, suggesting relatively short duration of the therapeutic regimen may have been effective in attenuating the glycemic status, with some improvement in insulin sensitivity, but the normalization of the lipid profiles may require a longer treatment duration or a greater dose of the α-glucosidase inhibitor agent. In contrast, acarbose was effective in improving both glycemic and lipid parameters and in normalizing weight gain with the SU diet to that of ST fed controls.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A previous in vitro study suggested that in tumor cell lines, osteopontin stimulates MMP9 up-regulation via FAK, ERK, and NF-κB-dependent signaling pathways, which promote cytoskeletal organization, cell motility, and cell migration [ 12 ]. Furthermore, our previous study showed that diabetic conditions (OH) induced A7r5 cell migration and proliferation-related signaling and that acarbose treatment could potentially prevent atherosclerosis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%